INTEGRASI MODERASI BERAGAMA SEBAGAI HIDDEN CURRICULUM DALAM PENGEMBANGAN KURIKULUM DI PERGURUAN TINGGI AGAMA - adi HR, sabri (IAIN Bone, 2023)
Â Â This research is motivated by the development of exclusivism, extremism, and radicalism, as well as the decline of religious harmony in society, especially in religious higher education. The focus of this paper is to determine the urgency of religious moderation as a hidden curriculum in religious higher education, as well as to find a model of integrating religious moderation as a hidden curriculum in curriculum development. This research is a literature review, and data is collected through document analysis, both in soft copy and written form, and analyzed qualitatively. The results show that radical ideologies emerge in an organized manner and are related to certain politics, social, and cultural aspects. Therefore, it is urgent to develop the value of religious moderation as a hidden curriculum and to make efforts to curb the development of radical ideologies in religious higher education. There are two models that can be operationalized in religious higher education. First, religious moderation as a hidden value in curriculum development using a correlated curriculum organization. Second, religious moderation as a hidden curriculum is derived from CPL to CPMK. The attitude achievements formulated in the regulations of the Minister of Education and Culture of the Republic of Indonesia No. 3 of 2020 are translated more specifically into CPMK, thus allowing the value of religious moderation to be included as CPMK.